Survey and first report of Acanthamoeba T4 genotype in natural spring water resources in the Black Sea, Turkey. (16th December 2021) - Karaman, Ulku; Koloren, Zeynep; Karanis, Panagiotis
Abstract: Infection with Acanthamoeba spp . may result in granulomatous amoebic encephalitis and Acanthamoeba keratitis. Water is an important habitat where Acanthamoeba species thrive. Therefore, studying the occurrence of this free-living amoeba in water sources will help understand the infection dynamics. The aim of the study was to survey and report on the presence of Acanthamoeba spp. in water resources from the Ordu and Giresun provinces in Black Sea. Acanthamoeba spp. was found in 1/17 natural spring water samples from Ordu and in 2/18 from Giresun. Acanthamoeba species were not detected in any of the investigated tap water samples. Sequencing of the (SSU) rDNA gene resulted in the identification of haplotype I ( Acanthamoeba genotype: KJ094684). T4 (8.6%) was the only isolated genotype in both Ordu and Giresun provinces. This is the first report of Acanthamoeba T4 genotype in natural spring water resources in the Black Sea. The occurrence of Acanthamoeba species in natural spring water sources should be considered as a potential risk for human infection, especially to high-risk populations. HIGHLIGHTS: Pathogenic Acanthamoeba detection in natural spring water in Black Sea, Turkey. Identification of pathogenic Acanthamoeba genotypes in Black Sea, Turkey. First report of Acanthamoeba T4 genotype in natural spring water in Black Sea, Turkey. Acanthamoeba T4 genotype is natural spring water is a potential health risk for high-risk humans. Graphical Abstract